2019
DOI: 10.3390/w11112391
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Trichloroethylene with Photocatalyst-Coated Optical Fiber

Abstract: In this present study, we investigated the effect of photocatalyzation on the degradation of trichloroethylene (TCE) in the aqueous phase by a photocatalyst-coated plastic optical fiber (POF). Two light-emitting diodes (LEDs) with low light intensity were used as the light source and TiO2 and ZnO were used as photocatalysts, which were characterized by scanning electron microscope (SEM) and UV-Vis diffuse reflectance spectroscopy (DRS). The para-chlorobenzoic acid (pCBA) was used as the hydroxyl radical probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…This was due to higher energy and intensity of the solar light as compared to the low power of LED light used (50W). Similar finding was also reported by Chen et al [ 50 ] who reported improved photocatalytic degradation of trichloroethylene as the power of the LED light increased. In this study by Chen et al, the improvement in the activity of the Titania was justified by the increase in the number of active hydroxide radicals as a result of stronger excitation energy provided by the light.…”
Section: Resultssupporting
confidence: 90%
“…This was due to higher energy and intensity of the solar light as compared to the low power of LED light used (50W). Similar finding was also reported by Chen et al [ 50 ] who reported improved photocatalytic degradation of trichloroethylene as the power of the LED light increased. In this study by Chen et al, the improvement in the activity of the Titania was justified by the increase in the number of active hydroxide radicals as a result of stronger excitation energy provided by the light.…”
Section: Resultssupporting
confidence: 90%
“…It can be due to the in situ production of hydroxyl ions, these ions are responsible for the increase observed in the alkalinity of the liquid phase [ 52 ]. This increase in the pH value can have a positive effect, as several researchers have reported higher photocatalytic efficiency at basic pH values [ 53 , 54 ]. It was also observed that the values of total hardness, chlorides, and nitrates slightly decreased after the photocatalytic treatment.…”
Section: Resultsmentioning
confidence: 99%
“…73% efficiency was observed with the white light of 8 W, as compared to 92% with 24 W. Other researchers also noted the change in photocatalytic performance with the change in light intensity. 29,30 The authors stated that higher intensity is helpful in generating a higher number of radicals. Despite this fact, the photocatalytic performance was found to be decent under the light of lower power.…”
Section: Power Sourcementioning
confidence: 99%